Implementasi Pendidikan Karakter Dalam Pembelajaran Tema 2 Kelas III dan V Sekolah Dasar - Fadhliyah, Nurul; Sukarno, Sukarno; Yulisetiani, Septi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This research aims to describe the implementation of character education values in learning theme 2 in class III and V students of SD Negeri Pleret Kidul, the obstacles encountered in implementation, and efforts to overcome these obstacles. The subjects of this study were teachers of grades III and V at SD Negeri Pleret Kidul. This research is qualitative descriptive research with a case study approach. Data collection techniques in this study used observation, interviews, and documentation. Data on the implementation of character education in thematic learning was obtained from the teacher. Researchers made direct observations at schools to observe the implementation of character education in thematic learning. Data validity uses source triangulation. Data analysis used the Miles-Huberman interactive analysis model. The results showed that the teachers in grades III and V SD Negeri Pleret Kidul had implemented character education values in the implementation of learning theme 2 as evidenced by the integration of learning theme 2 with character education.